Wild bees (Hymenoptera: Apoidea) in urban ecosystem: Preliminary survey in the city of Bogotá and its surroundings - NATES-PARRA, GUIOMAR; PARRA-H, ALEJANDRO; RODRÍGUEZ, ANGELA; BAQUERO, PEDRO; VÉLEZ, DANNY (Revista Colombiana de Entomología, 2006)
The high altitude flat area of Bogotá is located at 2600 m elevation and has temperatures that oscillate between -5 and 25 ºC (average 14ºC). Based on archives, field notes, bibliographic review and a database from the Bee Research Laboratory of the National University in Bogotá (LABUN), information was obtained on the wild bees present in the city of Bogotá and nearby localities. In addition, surveys were made in different sites in the city and its surroundings, observations were taken directly in the field, and information was compiled on plants visited by bees in the study area. Forty bee species were found belonging to 18 genera and distributed among the five families recorded for the country. Halictidae and Apidae were the most speciose families. Among all bee species found, 82,5% are Neotropical in distribution and 25% typically Andean in distribution. Data is presented on the foraging behavior, nest architecture and external activity for some species of wild urban bees. Thygater aethiops and Caenohalictus sp. nest mainly in parks and near patches of ornamental plants, whereas Anthophora walteri nests in dry areas with little vegetation. Bees of the genus Bombus were found nesting outside of strictly urban boundaries. The most visited plants were mainly ornamental species belonging to the families Acanthaceae, Asteraceae, Caprifoliaceae, Solanaceae and Scrophulariaceae.